2022
DOI: 10.1021/acs.jpcb.2c06176
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Changes in Terminal Alkynes Provide Strong, Sensitive, and Solvatochromic Raman Probes of Biochemical Environments

Abstract: The C�C stretching frequencies of terminal alkynes appear in the "clear" window of vibrational spectra, so they are attractive and increasingly popular as site-specific probes in complicated biological systems like proteins, cells, and tissues. In this work, we collected infrared (IR) absorption and Raman scattering spectra of model compounds, artificial amino acids, and model proteins that contain terminal alkyne groups, and we used our results to draw conclusions about the signal strength and sensitivity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 73 publications
1
21
0
Order By: Relevance
“…Further, when we calculated the peak wavenumber and FWHMs with Lorentzian fitting, we observed red-shifting of the peak wavenumber in 90% DMSO. This can be explained in terms of the solvent effect, considering that Raman tags such as nitriles and alkynes are sensitive to the local environment (vibrational solvatochromism). Also, the peak broadening of 9CN-DEP at low DMSO concentration is consistent with the reported tendency that the nitrile peak width is broader in water than in organic solvent . On the other hand, the peak width of 9CN-DER tended to be narrower due to aggregate formation at low DMSO concentration (Figure S3 and Table S1).…”
Section: Resultssupporting
confidence: 71%
“…Further, when we calculated the peak wavenumber and FWHMs with Lorentzian fitting, we observed red-shifting of the peak wavenumber in 90% DMSO. This can be explained in terms of the solvent effect, considering that Raman tags such as nitriles and alkynes are sensitive to the local environment (vibrational solvatochromism). Also, the peak broadening of 9CN-DEP at low DMSO concentration is consistent with the reported tendency that the nitrile peak width is broader in water than in organic solvent . On the other hand, the peak width of 9CN-DER tended to be narrower due to aggregate formation at low DMSO concentration (Figure S3 and Table S1).…”
Section: Resultssupporting
confidence: 71%
“…While such strongly absorbing alkynes with long vibrational lifetimes are useful IR probes for nonlinear vibrational spectroscopy, they have not been widely used in biological studies. 244…”
Section: Alkyne Stretching Vibrationmentioning
confidence: 99%
“…In addition, Cho and co-workers , showed that addition of a heavy atom, such as silicon (Si) or selenium (Se), between the probe alkyne group and the parent molecule can significantly enhance the transition dipole moment and the vibrational lifetime of the corresponding CC stretching vibration. While such strongly absorbing alkynes with long vibrational lifetimes are useful IR probes for nonlinear vibrational spectroscopy, they have not been widely used in biological studies …”
Section: Vibrational Probesmentioning
confidence: 99%
“…(2) Wei and co-workers 137 demonstrated a hydrogen− deuterium exchange (HDX) strategy to sense local chemical and environment changes in cells (e.g., acidity) using terminal alkyne-tagged Raman probes, which is based on the idea that deuteration of the alkynyl hydrogen can cause a large red shift in its Raman peak (>100 cm −1 in their cases); in addition, they reported a strategy to generate alkyne Raman probes via photoinduced cyclopropenone caging, allowing them to perform multicolor live-cell SRS imaging and tracking; 150 (3) Numata and co-workers 151 demonstrated that terminal alkynebased Raman probes that mimic choline and octadecanoic acid can be used to track and quantify such metabolite's uptake and the corresponding metabolic pathways within intact Arabidopsis thaliana (A. thaliana) roots and tobacco Bright Yellow-2 (BY-2) culture cells; (4) Liu and co-workers 152 developed a urinary biomarker, which consists of two alkyne-containing moieties with one behaving as an internal standard and one acting as a disease responsive unit, for quantitatively monitoring cancer development in real time via surface enhanced Raman spectroscopy; and (5) Londergan and coworkers 153 demonstrated that the Raman signals arising from both aliphatic and aromatic terminal alkynes show strong solvatochroism and, hence, can be used to report local electronic interactions in proteins (i.e., via a genetically incorporable alkyne-containing nonnatural amino acid, such as p-ethynylphenylalanine). Furthermore, various strategies have been developed to increase the Raman scattering cross section of alkynes used in biological studies or expand their utilities.…”
Section: In Biological Sciencementioning
confidence: 99%
“…For example, they have been used to image and interrogate a wide variety of biological molecules, such as proteins, nucleic acids, glycans, and small metabolites, in live cells via stimulated Raman scattering (SRS) microscopy. Since this topic has been extensively reviewed, ,, below we only briefly discuss several recent studies in this area, highlighting the increased utility of the CC stretching vibration in biological science. For example, (1) Min and co-workers developed a new set of ultrabright and compact Raman-active nanoparticles (Rdots) that are composed of polyyne-based dyes (or other alkyne-containing molecules) and further demonstrated that, when used in conjunction with SRS microscopy, such Rdots can lead to a detection limit down to pM scale in solution and even allow single-particle imaging; (2) Wei and co-workers demonstrated a hydrogen–deuterium exchange (HDX) strategy to sense local chemical and environment changes in cells (e.g., acidity) using terminal alkyne-tagged Raman probes, which is based on the idea that deuteration of the alkynyl hydrogen can cause a large red shift in its Raman peak (>100 cm –1 in their cases); in addition, they reported a strategy to generate alkyne Raman probes via photoinduced cyclopropenone caging, allowing them to perform multicolor live-cell SRS imaging and tracking; (3) Numata and co-workers demonstrated that terminal alkyne-based Raman probes that mimic choline and octadecanoic acid can be used to track and quantify such metabolite’s uptake and the corresponding metabolic pathways within intact Arabidopsis thaliana ( A. thaliana ) roots and tobacco Bright Yellow-2 (BY-2) culture cells; (4) Liu and co-workers developed a urinary biomarker, which consists of two alkyne-containing moieties with one behaving as an internal standard and one acting as a disease responsive unit, for quantitatively monitoring cancer development in real time via surface enhanced Raman spectroscopy; and (5) Londergan and co-workers demonstrated that the Raman signals arising from both aliphatic and aromatic terminal alkynes show strong solvatochroism and, hence, can be used to report local electronic interactions in proteins (i.e., via a genetically incorporable alkyne-containing nonnatural amino acid, such as p -ethynylphenylalanine).…”
Section: Application Of Cc Stretching Vibration In Biological Sciencementioning
confidence: 99%